2013
DOI: 10.1371/journal.pone.0080741
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of PLAGL1-Specific CpG Site Methylation in Soft-Tissue Sarcomas

Abstract: Soft tissue sarcomas (STS) are rare, complex tumors with a poor prognosis. The identification of new prognostic biomarkers is needed to improve patient management. Our aim was to determine the methylation status of the 118 CpG sites in the PLAGL1 tumor-suppressor gene P1 CpG island promoter and study the potential prognostic impact of PLAGL1 promoter methylation CpG sites in STS. Training cohorts constituted of 28 undifferentiated sarcomas (US) and 35 leiomyosarcomas (LMS) were studied. PLAGL1 mRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Only select CpG units may be used as markers distinguishing CIN II/III from CIN I/normal samples (Figure 3 B). Consistent with our observation, other reports has demonstrated that aberrant DNA methylation of only specific CpGs within the CGI are responsible for the downregulation of gene expression [ 40 - 44 ], and more recently, a substantial number of studies reported a specific, single CpG can function as strong prognostic or predictive indicators in various cancers [ 28 , 45 - 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Only select CpG units may be used as markers distinguishing CIN II/III from CIN I/normal samples (Figure 3 B). Consistent with our observation, other reports has demonstrated that aberrant DNA methylation of only specific CpGs within the CGI are responsible for the downregulation of gene expression [ 40 - 44 ], and more recently, a substantial number of studies reported a specific, single CpG can function as strong prognostic or predictive indicators in various cancers [ 28 , 45 - 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Aberrant hypomethylation of ICR/P1 on the maternal allele results in overexpression of PLAGL1 and HYMAI, which accounts for about 20% of TNDM1 patients [51,53]. Moreover, recent studies have shown the association between the methylation status of PLAGL1 promoter on chromosome 6 and different types of cancer, e.g., ovarian cancer and soft-tissue sarcomas [108,109].…”
Section: Transient Neonatal Diabetes Mellitusmentioning
confidence: 99%
“…Meanwhile, aberrant DNA methylation has been regarded as one of the hallmarks of cancer tissues [35,36], alterations in DNA methylation also play a virtual role in the progression and development of STSs [20,21]. In addition, S. Peter Wu et all had confirmed that methylation-based classifier could be used to provide diagnostic assistance in bone sarcoma [18].…”
Section: Discussionmentioning
confidence: 99%
“…At present, as a promising molecular marker of STSs, abnormal DNA methylation appears in early detection, prognosis prediction, molecular classification [18,19]. Meanwhile, multiple biological studies have also clarified that a series of methylations in gene promoter sequences is correlated with the prognosis and progression of STSs patients [20][21][22]. Nevertheless, the prognostic value of these aberrantly methylation sites in STSs subtypes and the complex role of DNA methylation in distinct gene regions are still largely unclarified and require further validation in the prognostic role of DNA methylation in STSs.…”
Section: Introductionmentioning
confidence: 99%